Heart failure in the elderly: diastolic heart failure, medical therapy, women and end-of-life care. (August 2010) - Dhesi, Pavittarpaul; Willix, Robert D; Phan, Anita; Tehrani, Faramarz; Daneshvar, Daniel; Schwarz, Ernst R
Heart failure is a leading source of cardiovascular morbidity and mortality in the world. The disease is particlularly prevalent among older patients. The elderly population suffers a high disease burden associated with the distinctive pathophysiology and associated symptoms. There are several challenges healthcare providers face in the management of older patients with heart failure. The present article provides some thoughts on issues in heart failure management in older patients with an emphasis on diastolic heart failure, concerns of polypharmacotherapy, undetected and untreated heart failure among women, and end-of-life care concerns that are relatively unique to an elderly heart failure population. With the expected increase in the number of patients with heart failure and the fact that they might live longer but may suffer more, further efforts are required to aid understanding of the specific needs and challenges for healthier aging, even with a chronic and incurable disease.